Saltmarsh flow and vegetation data - Tim Marjoribanks; Dimitri Lague; Richard Hardy; Richard Boothroyd; Jerome Leroux; Cendrine Mony; Sara Puijalon (2019)
Data for the paper:Marjoribanks, T. I., Lague, D., Hardy, R. J., Boothroyd, R. J., Leroux, J., Mony, C., & Puijalon, S. ( 2019).Flexural rigidity and shoot reconfiguration determine wake length behind saltmarsh vegetation patches. Journal of Geophysical Research: Earth Surface, 124.